The Eden Test - Sternbergh, Adam (Flatiron Books, 2023)
"Adam Sternbergh brings his wit, humor, and a Hitchcockian sense of dread to What Have We Done, a chilling, surprising, and wholly entertaining portrait of a marriage on the brink. Seven Days. Seven Questions. Forever Changed. That's how The Eden Test, a week-long getaway, advertises itself for couples in trouble. And that's what Daisy, a talented actress, has signed up for, in the hopes of saving her marriage. It's a tall order, seeing as her husband Craig plans on leaving her for another woman. In fact, his bags are packed in the back of the car as he drives to the cabin in the woods in upstate New York. But spending time together is nice and Craig enjoys the solitude of the cabin, the nearby lake, and the apple orchard. He'd even like the quirky small town, if it wasn't for a few locals calling him a city idiot. Maybe this could actually work? But Craig doesn't know that Daisy, one of the best actresses no one has ever heard of, has her own secrets, including a burner phone she's been using to text someone else. Their marriage was already under duress but now the lies and secrets are coming so fast it's hard to keep up..."--